PEMISAHAN Zn MENGGUNAKAN LIGAN ASAM POLI(EUGENOKSI ASETAT) DENGAN METODE EKSTRAKSI CAIR-CAIR - La Harimu (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2011)
Separation of Zn with poly(eugenoxyacetic acid) with liquid-liquid extraction have been counducted in four step that were determination of the optimum pH, determine optimum ligan volume, determine optimum extraction time, and determine optimum Zn concentration. The concentration of Zn in water phase was determined using Atomic Absorption Spectroscopy (AAS). %E is the number that show the effectiveness the extraction proccess. If the %E is bigger, it show that the extraction proccess is effective, and vice versa. The optimum condition for ion separation was occurred at pH 6, the carrier volume was optimum at 5 mL (1 Ã— 10-3 M), the optimum extraction time was 24 hours and the concentration range of metals ion accurately extracted was 1 Ã— 10-4 - 5 x 10-4 M with %E was 97.71%